INCRЕASE OF EFFICIENCY INDEX OF LOGISTIC SYSTEM IN REPUBLIC OF BELARUS - R. B. Ivut; N. V. Stephanovich; O. I. Moysak (Наука и техника)
In order to improve position of the Republic of Belarus in the rating of the World Bank by a logistics index a problem pertaining to creation and development of complex logistics system which will allow to change radically the situation in the country’s market of services and to receive considerable foreign-currency resources in the Republic budget becomes rather actual one. Keeping in view this purpose it is necessary to raise efficiency of customs procedures, quality of transport infrastructure and information technologies, make international deliveries more accessible with due account of logistical environment development. The proposed measures must stimulate development of the national logistics system which permits quickly to develop transit transportations with minimum expenses